A preclinical microbeam facility with a conventional x-ray tube - Bartzsch, Stefan; Cummings, Craig; Eismann, Stephan; Oelfke, Uwe (Medical physics, 2016)
Purpose: Microbeam radiation therapy is an innovative treatment approach in radiation therapy that uses arrays of a few tens of micrometer wide and a few hundreds of micrometer spaced planar x-ray beams as treatment fields. In preclinical studies these fields efficiently eradicated tumors while normal tissue could effectively be spared. However, development and clinical application of microbeam radiation therapy is impeded by a lack of suitable small scale sources. Until now, only large synchrotrons provide appropriate beam properties for the production of microbeams. Methods: In this work, a conventional x-ray tube with a small focal spot and a specially designed collimator are used to produce microbeams for preclinical research. The applicability of the developed source is demonstrated in a pilot in vitro experiment. The properties of the produced radiation field are characterized by radiochromic film dosimetry. Results: 50 μm wide and 400 μm spaced microbeams were produced in a 20 × 20 mm2 sized microbeam field. The peak to valley dose ratio ranged from 15.5 to 30, which is comparable to values obtained at synchrotrons. A dose rate of up to 300 mGy/s was achieved in the microbeam peaks. Analysis of DNA double strand repair and cell cycle distribution after in vitro exposures of pancreatic cancer cells (Panc1) at the x-ray tube and the European Synchrotron leads to similar results. In particular, a reduced G2 cell cycle arrest is observed in cells in the microbeam peak region. Conclusions: At its current stage, the source is restricted to in vitro applications. However, moderate modifications of the setup may soon allow in vivo research in mice and rats.
Gesehen am 19.08.2020